Constitutional Interpretation and Gender Equality: Analyzing the High Court Division’s Landmark Decision on Maternal Guardianship in Bangladesh - Jusi, Asmaul Hosna; Mohi Uddin (Al-Daulah : Jurnal Hukum Pidana dan Ketatanegaraan, 2024)
Research Objective: This research examines the significant ruling by the High Court Division of Bangladesh’s Supreme Court on January 24, 2023, recognizing mothers as legal guardians of their children. The study analyzes this major shift from traditional frameworks recognizing fathers as primary custodians to a system emphasizing equal maternal rights in child custody matters. Research Method: The methodology employed a comprehensive socio-legal analysis combining normative legal examination, case law analysis, and interdisciplinary perspectives. Multiple analytical approaches examined statutory provisions, constitutional articles, and judicial precedents, integrating sociological and psychological perspectives to assess broader societal implications. Results. The Court’s ruling represents a fundamental transformation in Bangladesh’s family law tradition, establishing legal precedent for maternal guardianship rights. Analysis demonstrates a documented shift from patriarchal custody norms toward gender-neutral guardianship frameworks aligned with constitutional equality principles. Findings and Implications. Research reveals multidimensional implications across legal, social, and psychological domains. Legal implications establish constitutional recognition of equal maternal custody rights. Social implications demonstrate the transformation of traditional gender roles and women’s empowerment within family structures. Individual implications include enhanced parenting choices, decision-making authority, and improved access to education and healthcare services. Conclusion. This landmark ruling represents a pivotal moment in women’s legal status evolution within Bangladesh’s family law system, fundamentally altering traditional structures by challenging patriarchal norms and highlighting changing women’s roles within legal contexts. Contribution. The study provides comprehensive documentation of family law transformation, contributing to legal scholarship, gender studies, and social policy development by demonstrating how judicial decisions catalyze broader social change. Limitations and Suggestions. Research recommends additional legal reforms to protect children’s rights and addresses implementation challenges, suggesting comprehensive policy amendments to ensure effective transformation of family law practices in Bangladesh.